In-situ preparation of water chestnut-based carbon aerogel and its application in binder-less electric double layer electrode and stress sensing. (November 2020) - Zhang, Shaohui; Wu, Haodi; Zhang, Haifeng; Liu, Zeng; Zhang, Long; Chen, Jiafan; Zhou, Quan; Pan, Gebo
Abstract: The water chestnut-based carbon aerogel (WCA) that was directly in-situ prepared via a simple one-step hydrothermal method. The as-prepared WCA had excellent electrochemical properties as a binder-less electric double layer (EDL) electrode in SCs. Specifically, the WCA after annealing exhibited a superior mass specific capacitance of 343.4 F/g at 0.5 A/g in 3 M KOH. Also, the WCA displayed ultra-high capacitance retention rate, which significantly remained close to 100% after 20, 000 cycles and still maintained 98.3% after 40, 000 cycles. In addition, the green and sustainable WCA yet demonstrated ultra-high sensitivity (42.8 kPa −1 ) and recoverable performance, which had potential application value in flexible pressure sensors. After 3000 compression-release cycles, the recovery rate exceeded 90%. Highlights: ● Water Chestnut-based Carbon Aerogel (WCA) was prepared via one-step hydrothermal method. ● The WCA exhibited a superior mass specific capacitance of 343.4 F/g at 0.5 A/g. ● The WCA displayed ultra-high capacitance retention rate, which still maintained 98.3% after 40, 000 cycles. ● After 3000 compression-release cycles, the recovery rate exceeded 90%.